2017
DOI: 10.1002/art.40364
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: A Phase IIb Trial of a Novel Extended‐Release Microsphere Formulation of Triamcinolone Acetonide for Intraarticular Injection in Knee Osteoarthritis

Abstract: Objective FX006 is a novel, microsphere‐based, extended‐release formulation of triamcinolone acetonide for intraarticular (IA) injection designed to maintain treatment concentration in the joint and provide prolonged analgesic benefits in patients with osteoarthritis (OA) of the knee. This study was undertaken to compare the analgesic benefits of 2 FX006 doses with saline placebo injection.MethodsIn this phase IIb study, participants with knee OA (Kellgren/Lawrence grade 2–3) and average daily pain (ADP) inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
85
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(92 citation statements)
references
References 14 publications
(15 reference statements)
7
85
0
Order By: Relevance
“…The differences in SF TA concentrations observed in this studydGMs of 3590.0 and 290.6 pg/mL at Week 6 and Week 12, respectively, for FX006 and 7.7 pg/mL at Week 6 for TAcsdlikely constitute the basis for pharmacologic differentiation and provide a rational hypothesis for between-treatment efficacy differences observed in Phase 2/3 trials 37,39,47 39 . These effects are clinically important; post-hoc analyses demonstrated that the improvements in all WOMAC subscale scores afforded by FX006 exceeded the minimum clinically important improvement (MCII) thresholds utilized by the American Academy of Orthopedic Surgeons (AAOS) 39e42 .…”
Section: Synovial Concentrations Of Ta E Clinical Implicationsmentioning
confidence: 55%
See 1 more Smart Citation
“…The differences in SF TA concentrations observed in this studydGMs of 3590.0 and 290.6 pg/mL at Week 6 and Week 12, respectively, for FX006 and 7.7 pg/mL at Week 6 for TAcsdlikely constitute the basis for pharmacologic differentiation and provide a rational hypothesis for between-treatment efficacy differences observed in Phase 2/3 trials 37,39,47 39 . These effects are clinically important; post-hoc analyses demonstrated that the improvements in all WOMAC subscale scores afforded by FX006 exceeded the minimum clinically important improvement (MCII) thresholds utilized by the American Academy of Orthopedic Surgeons (AAOS) 39e42 .…”
Section: Synovial Concentrations Of Ta E Clinical Implicationsmentioning
confidence: 55%
“…These findings are consistent with those observed in larger Phase 2/3 clinical trials of FX006, in which a single IA FX006 injection demonstrated systemic and local safety profiles generally similar to placebo and TAcs, and no post-injection flares were observed. 37,39,47 Despite prolonged TA joint residence associated with microsphere delivery, index-knee related AEs were limited to two FX006treated patients (Grade-1 arthralgia, Grade-2 patellofemoral pain syndrome). This lack of adverse local effect is not unexpected given that the FX006 PLGA matrix degrades to oligomeric poly-acid units, then to lactic and glycolic acids 48 , followed by elimination as carbon dioxide and water.…”
Section: Safety Data E Clinical Implicationsmentioning
confidence: 99%
“…The therapeutic efficacy of IA triamcinolone acetonide ER in patients with OA pain of the knee has been evaluated in three randomized, double-blind, multicentre studies, of which two were dose-ranging phase II ( n = 228) [ 26 ] or IIb ( n = 306) [ 27 ] trials and the other a phase III trial ( n = 484) [ 28 ]. This section focuses on the trials [ 27 , 28 ] that evaluated the dose (32 mg) and injection volume (5 mL) of triamcinolone acetonide ER that was approved in the USA for the management of OA pain of the knee [ 11 ].…”
Section: Therapeutic Efficacymentioning
confidence: 99%
“…It is well-known that exogenous IAI of hyaluronate is valid as a treatment for the symptoms of knee osteoarthritis [15]. IAI of the novel, microsphere-based, extended-release formation of triamcinolone acetonide leads to a prolonged reduction in symptoms of osteoarthritis [16]. Deducted from studies above, IAI of analgesic cocktail may also play a role in pain relief after TKA.…”
Section: Introductionmentioning
confidence: 99%